Inflammatory state exists in familial amyloid polyneuropathy that may be triggered by mutated transthyretin - Genki Suenaga (Nature Portfolio, 2017)
Abstract The relationship between familial amyloid polyneuropathy (FAP), which is caused by mutated transthyretin (TTR), and inflammation has only recently been noted. To determine whether inflammation is present in FAP carriers and patients, serum interleukin (IL)−6 concentration in 57 healthy donors (HD), 21 FAP carriers, and 66 FAP patients was examined, with the relationship between IL-6 and TTR assessed in each group by multiple regression analysis and structural equation models (SEM). Compared with HD, IL-6 concentration was elevated in FAP carriers (p = 0.001, 95% CI 0.398–1.571) and patients (p = 0.002, 95% CI 0.362–1.521). Further, SEM indicated a positive relationship between IL-6 and TTR in FAP carriers (p = 0.010, 95% CI 0.019–0.140), but not in HD and FAP patients. In addition, we determined whether TTR induces production of pro-inflammatory cytokines ex vivo. HD-derived CD14 + monocytes and induced pluripotent stem cell-derived myeloid lineage cells from a HD and FAP patient dose-dependently produced IL-6 under mutated and aggregated TTR conditions, compared with wild-type TTR. In conclusion, FAP carriers and patients are in an inflammatory state, with the presence of mutated TTR being a trigger of inflammation, especially in FAP carriers.